Recovering from service failure: does satisfaction fortify brand trust? - Abd Rashid, Muhammad Hafiz; Sh. Ahmad, Fauziah (2014)
Most companies across the globe are aware the impact of service failure towards the reputation and long term profitability of their businesses. However, not all companies are fully prepared for such transgression.As a result of service failure, customers will be dissatisfied and lost trust towards the company’s brand.Therefore, a study on service recovery is critical to investigate its influence in building customer satisfaction and brand trust.Justice theory is one of the most prominent theoretical foundations in service recovery studies. Thus, the three dimensions of justice theory which includes distributive justice, procedural justice, and interactional justice will be employed in this study.It is expected that this conceptual paper will provide platform for practitioners and researchers who are interested to explore the importance of service recovery in retaining customers and increase profitability.